Household level spillover effects from biofuels - Olivia Riera; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2014)
The indirect effects of biofuels are mostly considered negative. In this paper, we argue that there may be a positive indirect effect of biofuels on food security and poverty. Our analysis shows that the introduction of castor production for biofuel in a poor country as Ethiopia can significantly improve food productivity of rural households who produce raw material for biofuel production. This spillover seems particularly linked to enhanced access to inputs and technical assistance which were provided as part of biofuel feedstock production contracts. Our results thus help nuancing the view that biofuels necessarily harm smallholders' food security.
Keywords: 330; biofuels; contract farming; productivity; spillovers; Ethiopia